TRANSFORMASI LIMBAH TUTUP BOTOL PLASTIK MENJADI TAS KREATIF UNTUK KEMANDIRIAN EKONOMI DAN PELESTARIAN LINGKUNGAN - Fadhilah, Raudhatul; Utami, Putri Yuli; Kurniasari, Fita; Masriani, Masriani; Ihwan, Andi; Jumarang, Ishak; Tiara, Tiara; Herniawati, Herniawati; Tari, Sultra; Gibran, Muhammad; Maftuh, Irfan (Jurnal Abdi Insani, 2025)
Desa Sungai Rasau faces issues with plastic waste accumulation, particularly bottle cap waste, which poses environmental risks due to its non-biodegradable nature. The Kosabangsa Program was initiated as a solution to address this problem while also fostering entrepreneurial skills among students at Madrasah Ibtidaiyah Swasta Nahdhotul Athfal. Through a cross-sectoral collaborative approach, the program involves universities, schools, and the local community in transforming plastic bottle cap waste into creative bags. The applied methods include training, hands-on product creation, and marketing guidance. The results demonstrate a significant skill improvement, with 75% of participants able to independently create the bags and 90% reporting enriched learning experiences due to the collaboration. This program has the potential to serve as a sustainable model that integrates education, economic empowerment, and environmental awareness among students.